Modelling of cryogenic cooling system design concepts for superconducting aircraft propulsion - Palmer, Joe; Shehab, Essam (Institution of Engineering and Technology (IET), 2016)
Distributed propulsion concepts are promising in terms of improved fuel burn, better aerodynamic performance, and greater control. Superconducting networks are being considered for their superior power density and efficiency. This study discusses the design of cryogenic cooling systems which are essential for normal operation of superconducting materials. This research project has identified six key requirements such as maintain temperature and low weight, with two critical components that dramatically affect mass identified as the heat exchanger and compressors. Qualitatively, the most viable concept for cryocooling was found to be the reverse-Brayton cycle (RBC) for its superior reliability and flexibility. Single- and two-stage reverse-Brayton systems were modelled, highlighting that double stage concepts are preferable in specific mass and future development terms in all cases except when using liquid hydrogen as the heat sink. Finally, the component-level design space was considered with the most critical components affecting mass being identified as the reverse-Brayton compressor and turbine.
Keywords: Aircraft power systems; Aerodynamics; Brayton cycle; Compressors; Cryogenics; Heat sinks; Electric propulsion; Aerospace propulsion; Aerospace materials; Heat exchangers; Superconducting materials; Cooling